Unconditioned Superstition and Sports Bar Fans. Issue 1 (2nd January 2016) - Hanks, Lydia; Zhang, Lu; McGinley, Sean
Abstract : This study investigates whether inducing a superstitious belief in a consumer by suggesting a relationship between the consumer's purchase behavior and a specified outcome could influence consumer behavior. It also examines the moderating role of preconsumption mood in processing the information. Using information processing theory as a framework, hypotheses were developed using hypothetical scenarios and surveys. Our results demonstrated that participants in the positive mood condition reported higher expectations for the team's performance, more positive attitude, and stronger intent to purchase when the ads contained the superstition cue, whereas participants in the negative mood condition did not. These results expand the literature on superstitious consumer behavior by demonstrating that companies can not only address superstitions that consumers already hold, but can also induce superstitious beliefs in customers. By doing so, managers and marketers may be able to positively influence consumers' attitudes toward the company and loyalty behaviors.